A STUDY ON LATEX DRYING CHARACTERISTICS WITH DIFFERENCE OF THICKNESS USING GREENHOUSE EFFECT DRYER - Zulfikar Akbar (The University of Lampung, 2015)
Latex just been tapped has a high level ofmoisture content. To be useful for production, latex should be dried toreducewater content. Latex drying by rubber farmers is commonly to do conducted in opened areas for 14 dayswith a very thick size of latex. Therefore, we should be solutions to make latex drying faster. This research, latexdryingwas treatment by using greenhouse effect dryerwith difference of thickness. The aims of this researchwasto find out characteristics of latex drying using dimension of greenhouse effect dryer is 150 x 70 x 120 cm. Latexwas coagulated on containers, with dimension of containers is 40 x 10 x 15 cm. Latex was formed with anequipmentwhich intervals of 2, 1.5, and 1 cmand thenslabwas dried. Result of this research, latexwas driedwithgreenhouse for 9 hour/day for 6 days along. Temperatures of greenhouse effect dryer ranged from30 to 500Cwithrelative humidity of approximately 47%. The treatment with thickness of 2, 1,5 and 1 cm has final moisturecontent respectively were 9.53%, 8.96%, and 5.87%bb, and drying acceleration during drying process were0.3773%, 0.4119%, and 0.4445%w/w / day.Keywords :DryingAcceleration, GrenhouseDryer, Latex,Moisture Content, Thickness